Value-at-Risk: Applying Extreme Value Approach to Measuring Financial Markets of the Southeast Asian Countries - Chin, Wei Hoong (2012)
This dissertation is generally based on the paper by (Ho et al., 2000) to identify the VaR values in six countries of the Southeast Asia (SEA) during and prior to the recent global financial crisis in 2007-08. The main differences between this dissertation and Ho, et al. (2000) paper are the investigated Asian countries which includes Indonesia, Japan, Korea, Malaysia, Thailand, and Taiwan in the range of time period from 1984 – 1998. However, this dissertation involves countries such as Malaysia, Indonesia, the Philippines, Thailand, Singapore, and Vietnam from the year 2000 – 2011. Extreme Value Theory (EVT) is applied in both researches to model tail distributions of the market condition and Value-at-Risk (VaR) values were found to be more sensible and satisfactory with EVT approach compared to the traditional approaches, i.e. variance-covariance and historical simulation as the investigated market indexes exhibit leptokurtic returns. The parameter estimates of the maxima and minima series for each index are analyzed and VaR values are obtained based on the componentwise block maxima, i.e. Generalized Extreme Value approach (GEV) of 10-day and 20-day block length. Furthermore, the 2007-08 financial turmoil is discovered to have rather subtle impact towards the SEA region compare to the Asian financial crisis investigated by (Ho et al., 2000). The Ho, et al. (2000) paper includes back testing analysis on the VaR measures and discovered that EVT approach has the least exceedance or violations. Nevertheless, in this dissertation bivariate extreme value analysis is performed instead of VaR measures evaluations and it suggests that the relationships of extreme events happening within Singapore, Malaysia, Indonesia, and Thailand are rather strong during the financial crisis.